Neural correlates of frailty in cognitively healthy adults: A multimodal imaging study - Ilaria Parrotta; Lorenza Maistrello; Giorgio Arcara; Dante Mantini; Giovanni Lazzaro; Sonia Montemurro; Nicola Filippini (PLoS ONE, 2025)
Objective Frailty has emerged as prevalent condition in ageing. While frailty has been assessed through physical and functional criteria, recent studies have explored the link between cognitive decline and frailty, which remains complex and warrants further investigation. Our aims were to compare differences at the brain level between robust and frail older people without dementia and to explore possible associations between brain measures and cognitive performance assessed with neuropsychological tests. Methods Using data from the “CAM-Cam” project that recruited a community dwelling population, we identified robust and frail participants based on the Rockwood Frailty index. Magnetic Resonance Imaging was performed to probe the interplay between physical frailty and cognitive health. The main aims were: (i) to identify differences in cognitive performance using the Cattell Culture Fair test and the Tip of the Tongue test and (ii) to assess voxel-wise group-related effects, using a general linear model design to investigate potential differences between our two study groups (“frail” and “robust”). Results Our findings revealed significantly smaller grey matter volume in frail individuals, primarily localized in cerebellar areas and in the right supramarginal gyrus. Diffusion magnetic resonance imaging scans showed diminished axial diffusivity values in frail participants, particularly in the corticospinal tract. Resting-state functional MRI showed increased functional connectivity values within the Default Mode Network (DMN) in frail individuals, relative to the robust group in parietal and cerebellar portions of the DMN. Moreover, we observed significant correlations between cognitive score and brain measures for our study groups. Conclusions The associations between cognitive test scores and anatomical and functional patterns in the brain highlight the complex interconnections between physical and cognitive aspects of frailty. This study brings novel insights into the early neurobiological markers associated with physical frailty in a cognitively healthy population.